Identification Chemical Compositions of Lemongrass Plant (Cymbopogon nardus L.) Dawan Tribe, Oenenu Village, North Central Timor Regency - Noviana Obenu; Eduardus Edi; Risna E. Adu (Jurnal Akademika Kimia, 2021)
Lemongrass (Cymbopogon nardus L.) is a local natural resource used by the Dawan tribe as an alternative for mosquito repellent. The utilization of these plants cannot be separated from the content of compounds found in these plants. Therefore, it is necessary to analyze the content of bioactive compounds from lemongrass (Cymbopogon nardus L.). This research method includes sample preparation, isolation and identification of compounds, and antioxidant activity analysis. The results of this study that there were three main components of citronella oil, namely geraniol, citronellol, and citronellal, with a higher percentage of geraniol, namely 18.82%. The compounds contained in lemongrass oil have a weak antioxidant activity with IC50 681.48 mg/mL.